A Naturalistic Study of Time to Recovery in Adults with Treatment-refractory Disorders. Issue 3 (3rd July 2021) - Perry, J. Christopher; Fowler, J. Christopher
Abstract : Objectives : Individuals with treatment-refractory disorders have high comorbidity. There is little information on whether recovery is possible and how long it might require. We focused on the individual's recovery using a broad measure of psychopathology, regardless of the variety of disorders present. Methods : We recruited 226 adults [mean age 31.0, SD = 10.3; 75.2% female] entering residential treatment for treatment-refractory disorders to delineate their course and outcome. Individuals received periodic Longitudinal Interval Follow-along Evaluation interviews for symptoms and functioning variables for up to 14 years. Periodic psychodynamic and relationship vignette interviews were rated with the Psychodynamic Conflict Rating Scales (PCRS) for a subgroup of 54 subjects. Outcome variables included modeled rates of change, final scores, time to recovery, and time to attaining healthy adaptive functioning, using Kaplan-Meier estimates from time-to-event analyses. Results : Recovery of PCRS Pathological Functioning occurred in 12 (22%) of 54 subjects rated: median time-to-recovery = 11.63 years (CI: 9.64– upper number not calculable). Eight (14.81%) subjects also developed healthy adaptive functioning, with the time-to-attainment for the first quartile at 10.95 years (CI: 7.87 - upper bound not calculable). Recovery from psychopathology was significantly associated with a median percentage recovered in the domains of symptoms (64.29%), functioning (87.50%), and psychodynamic functioning (50%). Although attaining healthy adaptive functioning was less common, it was highly associated with already achieving recovery from dynamic psychopathology, [OR = 57.40, CI 5.80 – 567.83, p = .0001]. Conclusions : These results provided convergent validation of recovery in psychodynamic psychopathology. Some recovered individuals also attained healthy adaptive functioning, which took somewhat longer.